PELAYANAN KESEHATAN GIGI DI PUSKESMAS (STUDI KASUS DI PUSKESMAS SUMBERSARI) - Kiswaluyo, K. (Fakultas Kedokteran Gigi Universitas Jember, 2013)
Public Health Center is a functional organization that organizes health effort that is comprehensive, integrated, equitable, acceptable and affordable to the public. Performance of health workers in govermment health care organizations is still low. Coverage of patients in dental clinics that are low performing dentist is not optimal. The research aims to find the services provided by the dentist at the health center Sumbersari in the period January to June 2012.